Pengaruh Pengalaman Pelanggan, Kesadaran Merek Dan Kepercayaan Konsumen Terhadap Minat Beli Konsumen Indomaret Batamindo Square Cabang Batam - Erika Pransiska Putri; Tiurniari Purba (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This research examines the influence of customer experience, brand awareness and consumer trust on consumer buying interest at Indomaret Batamindo Square. In the context of increasingly tight business competition, especially in the retail sector, identifying the factors that influence purchasing interest is very important for the company's sustainability. The aim of this research is to determine the extent of the influence of these three variables on consumer buying interest. The method used in this research is a quantitative approach by collecting data through questionnaires distributed to 385 respondents who shop at Indomaret Batamindo Square. Data analysis was carried out using multiple linear regression to test the relationship between independent and dependent variables. The research results show that customer experience has a significant positive influence on purchase intention, followed by brand awareness and consumer trust which also contribute significantly. Sales data shows fluctuations, with some months experiencing ups and downs indicating the need for improvements in customer service and experience. The conclusion of this research is that to increase consumer buying interest, Indomaret needs to focus on improving customer experience, strengthening brand awareness, and building consumer trust. Recommendations for management include improving store facilities and more effective promotions to increase brand awareness among consumers. It is hoped that this research can become a reference for developing more effective marketing strategies in the future.